Periodontal infection is a “silent killer”* - I Dewa Ayu Susilawati (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Periodontal infection contained at many pro-oxidatif toxity components which is easily spreading through flood circulation syslimicly, and potentially acts as antigent and induces inflamating response inflamation processes is a front line defence respons to infection. However it is very dangerous if inflamation is oceure is a vital asam such as in brain and heart, could be of a life threatering. The spreading of Periodontal infection through Blodd steam is usually asymoptpmatically. Thas patients are unaware that their left is in a thred Periodontal infection is a “silent killer”.